Penampilan Karakter Agronomis Dan Analisis Jalur Sifat Komponen Hasil Dan Hasil Padi Sawah Berprotein Tinggi: Agronomic Character Appearance And Path Analysis Of Yield Component And Yield Traits Of High Protein Wetland Rice - Pramana, Ayub (Agrifarm : Jurnal Ilmu Pertanian, 2023)
Improvement and establishment of high protein rice varieties need correlation analysis and path analysis to study the close relationship of quantitative characters and as a basis for selection programs. The purpose of this experiment was to determine the appearance of the agronomic characters of five high protein lowland rice lines and to determine the relationship between yield components and yields of high protein lowland rice. The experiment was carried out from August 2021 to December 2021 in Karawangkal Village, North Purwokerto District, Banyumas. The experimental design used was a randomized block design. Data were analyzed by F test and estimation of correlation parameters between characters. The variables observed were plant height, panicle length, flowering age, harvest age, number of tillers, number of productive tillers, weight of 1000 seeds, weight of grain per panicle, weight of grain per clump, weight of grain per plot, percentage of filled grain per panicle, number of grain. per panicle, the number of grain content per panicle. The results of this research resulted that the G39 x CH PKC-2, G39 x CH PKC-3, MKD Gandrung, GN 95 A and GN 95 B lines had the same agronomic appearance as the comparison varieties, namely, IR 64 and Ciherang. The character of the weight of grain content per panicle and the weight of 1000 seeds has a direct effect that is almost equivalent to the correlation, so that the character of the grain content weight per panicle and the weight of 1000 seeds can be used as the most effective selection criteria.